When language gets emotional: irony and the embodiment of affect in discourse - Filik, Ruth; Hunter, Christian Mark; Leuthold, Hartmut (Elsevier, 2015)
Although there is increasing evidence to suggest that language is grounded in perception and action, the relationship between language and emotion is less well understood. We investigate the grounding of language in emotion using a novel approach that examines the relationship between the comprehension of a written discourse and the performance of affect-related motor actions (hand movements towards and away from the body). Results indicate that positively and negatively valenced words presented in context influence motor responses (Experiment 1), whilst valenced words presented in isolation do not (Experiment 3). Furthermore, whether discourse context indicates that an utterance should be interpreted literally or ironically can influence motor responding, suggesting that the grounding of language in emo- tional states can be influenced by discourse-level factors (Experiment 2). In addition, the finding of affect-related motor responses to certain forms of ironic language, but not to non-ironic control sentences, suggests that phrasing a message ironically may influence the emotional response that is elicited.